Study of the influence of water gaps between fuel assemblies on the activation of an aeroball measurement system (AMS). (February 2020) - Konheiser, J.; Mueller, S.E.; Seidl, M.
Highlights: Estimation of the influence of the fuel gaps on the aeroball measurement systems. The Monte Carlo code MCNP6 was used for the calculations. The maximum impact of the water gap up to 1 cm was calculated on the activation rate. Real reactor core loading patters were investigated with different burnups. Abstract: The aeroball measuring system (AMS) at Siemens/KWU built pressurized water reactors is an important part of the in-core instrumentation. With the Monte Carlo program MCNP6 the effect of the water gap size between the fuel assemblies was determined with respect to the 51 V(n, γ) 52 V reaction rate in the AMS. A 3 × 3 matrix of identical fuel assemblies was used. The AMS were simulated in the central fuel assembly. By shifting the outer assemblies, different water gaps were created and the effects on the reaction rate were calculated for different burn-up and boron contents in the cooling water. It was found that the change of reaction rates can reach up to 10% for a gap maximum of 1 cm. The changes are largest for burn-up at 30 and 45 GWd/t. The results are an important piece of information to assess the possibility of detecting non-nominal water gaps during reactor operation.